Evaluation of fiber optic communication link using an eye test diagram - 505287 Nuradhiah Mohd Kamaludim; Rosly Abd Rahman, supervisor; Fakulti sains (2010)
Project paper (Sarjana Muda Sains (Fizik Tulen)) - Universiti Teknologi Malaysia, 2010